STUDI KOMPARASI KUAT GESER BALOK KASTELA MODIFIKASI DARI PROFIL IWF - Ali Murtopo; Achmad Rafi'ud Darajat; Herlita Prawenti (Reviews in Civil Engineering, 2020)
Castellated steel beam is an engineered profile of steel beams to optimize its flexural strength. The consequence of this engineering is that the shear strength becomes weak because there are openings in the web. Researches to improve the shear strength of castellated beams has been carried out by modification these beams. Comparison is needed to determine the most optimal of castellated steel beam modification shear strength. The comparative method is carried out on existing research of modified castellated steel beams made from 150x75x7x5 IWF steel profiles, modifications in the form of openings engineering and the addition of stiffeners to openings and static testing. Types of beams that are compared includes original castellated beam, original castellated beam with lateral stiffeners, modified castellated beam with elbow steel stiffeners, modified castellated beam with reinforced steel diagonal stiffeners, and modified castellated beam with full rectangular openings and reinforced steel diagonal stiffeners. The comparison results show that modified castellated beam with full rectangular openings and reinforced steel diagonal stiffener have the most optimal shear strength with an increase of 146.54% compared to the original castellated beam.